China and Latin America: Mutual benefits or asymmetric relationship? - Vergara Crespo, Rubén Alfonso (2022)
With China’s rapid growth, it is worth considering whether or not the country has challenged the United States, which for decades was the hegemonic power in much of Latin America. Posed in international studies, these questions are viewed from a Western perspective, arguably ethnocentric and universalist, which understands the international context as one of allies and enemies, center and periphery. Thus, it is difficult to understand a global rearrangement involving a non-Western actor. There seems to be no other way of understanding peaceful coexistence without involving the dominant and dominated relationship. Therefore, this paper seeks to explain whether a strategic relationship, fostered based on equal relationships for mutual benefit, is possible, without thinking about the soft or strong power notion that characterized the international order of the 20th Century. For the approach, a qualitative analytical-descriptive methodology is used.